Flow-Mediated Factors in the Pathogenesis of Hypoplastic Left Heart Syndrome - Anum Rahman; Rajiv R. Chaturvedi; John G. Sled (Journal of Cardiovascular Development and Disease, 2022)
Hypoplastic left heart syndrome (HLHS) is a life-threatening congenital heart disease that is characterized by severe underdevelopment of left heart structures. Currently, there is no cure, and affected individuals require surgical palliation or cardiac transplantation to survive. Despite these resource-intensive measures, only about half of individuals reach adulthood, often with significant comorbidities such as liver disease and neurodevelopmental disorders. A major barrier in developing effective treatments is that the etiology of HLHS is largely unknown. Here, we discuss how intracardiac blood flow disturbances are an important causal factor in the pathogenesis of impaired left heart growth. Specifically, we highlight results from a recently developed mouse model in which surgically reducing blood flow through the mitral valve after cardiogenesis led to the development of HLHS. In addition, we discuss the role of interventional procedures that are based on improving blood flow through the left heart, such as fetal aortic valvuloplasty. Lastly, using the surgically-induced mouse model, we suggest investigations that can be undertaken to identify the currently unknown biological pathways in left heart growth failure and their associated therapeutic targets.